Psikoedukasi “Remaja MUDA” untuk Meningkatkan Asertivitas Anti-Seks Pranikah - Yenny Sandria Alexander; Bhina Patria (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to increase the understanding of sexuality at the age of puberty through